2008
DOI: 10.1016/j.ejheart.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphodiesterase‐5 inhibition by sildenafil in the pressure overloaded right heart

Abstract: Background: Sustained pressure overload of the right ventricle (RV) causes RV hypertrophy and failure. Cyclic-GMP has previously been shown to modulate left ventricular hypertrophy. Aim: To evaluate the effects of sildenafil, a phosphodiesterase-5 (PDE5) inhibitor elevating c-GMP, on myocardial hypertrophy and function in rats with RV hypertrophy. Methods: Rats were pulmonary trunk banded (PTB) and randomized to receive sildenafil (SIL) or vehicle (VEC) for three (n = 14) and nine weeks (n = 18). In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
3
42
0
1
Order By: Relevance
“…These observations have been confirmed by REX et al [29]. Two recent papers studied the effects of chronic treatment of sildenafil in a model where RV pressure overload was induced by pulmonary artery banding [30,31]. Both studies reported an increase in RV hypertrophy and/or improvement of RV function, which implies that there is a direct effect of sildenafil on the heart.…”
Section: Cardiac Effects Of Current Pah Medicationsupporting
confidence: 65%
“…These observations have been confirmed by REX et al [29]. Two recent papers studied the effects of chronic treatment of sildenafil in a model where RV pressure overload was induced by pulmonary artery banding [30,31]. Both studies reported an increase in RV hypertrophy and/or improvement of RV function, which implies that there is a direct effect of sildenafil on the heart.…”
Section: Cardiac Effects Of Current Pah Medicationsupporting
confidence: 65%
“…Furthermore, the biological effects for Sildenafil may differ depending on the experimental setup. A recent report by Andersen et al (2) has shown that high-dose Sildenafil treatment (100 mg ⅐kg Ϫ1 ⅐day Ϫ1 ) in a model for pulmonary trunk banding was not able to attenuate PAH development; in fact, it increased RV hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 The rats were placed on a heating pad during the procedure to maintain body temperature at 37˚C. The pulmonary trunk was accessed through a thoracotomy on the left side of the sternum.…”
Section: Pulmonary Trunk Bandingmentioning
confidence: 99%
“…Treatment with phosphodiesterase type 5 (PDE-5) inhibitors has been demonstrated to attenuate LV hypertrophy and improve LV function in mice, 1 but this effect was not found in rats with pressure overload-induced RV hypertrophy. [2][3][4] Sildenafil failed to inhibit RV hypertrophy, but some improvement in RV contractile function was seen in long-term sildenafil treatment. The improved function could possibly be explained by direct inhibition of PDE-5 in RV cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%